MANAJEMEN PELAKSANAAN MATA PELAJARAN BAHASA ARAB MTS HADIL ISHLAH - al gofari, Ziki; Fitriani, Laily (Lisanul Arab: Journal of Arabic Learning and Teaching, 2021)
Management of the implementation of Arabic subjects is an attempt to direct, mobilize and motivate members or subordinates in an organization to achieve goals. in this case the principal as a manager in the school must be able to direct, mobilize and motivate Arabic teachers in particular and generally staff or other teachers at school, besides that the teacher as the implementer of learning Arabic subjects must also be able to make implementation of effective and attractive learning using methods and techniques that are easy to understand by students and can take advantage of existing facilities and media and no less important, namely the teacher must be able to master the teaching material implementation management at MTs. Hadil Ishlah, the research method used is a qualitative method with a case study approach, and data collection techniques, namely by interview, observation and documentation, the results of the study explain that the management of the implementation of Arabic subjects in MTs. Hadil Ishlah includes three things, namely: 1) leadership, to achieve the goals of the school organization the principal as a manager in the school always provides guidance, direction and supervision, as well as a democratic teacher leadership style. 2) motivation, in addition to the principal, the teachers at the school also always provide motivation to students in the form of praise, salary, gifts, etc. 3) communication, as for the communication used at school is very good so that there is good cooperation between members of the school organization. Manajemen pelaksanaan mata pelajaran Bahasa Arab adalah usaha untuk mengarahkan, menggerakkan dan memotivasi anggota ataupun bawahannya dalam suatu organisasi untuk mencapai tujuan. dalam hal dalam hal ini kepala sekolah sebagai manajer di sekolah harus mampu mengarahkan, menggerakkan serta memotivasi guru bahasa Arab secara khusus dan umumnya staf atau guru-guru lain yang ada disekolah, selain itu juga guru sebagai pelaksana pembelajaran mata pelajaran bahasa arab juga harus mampu membuat pelaksanaan pembelajaran yang efektif dan menarik dengan menggunakan metode dan teknik yang mudah dipahami oleh siswa serta dapat memanfaatkan fasilitas dan media yang ada dan tidak kalah pentingnya yaitu guru harus mampu menguasai materi bahan ajar, Penelitian ini bertujuan untuk mengetahui bagaimana implementasi dan faktor-faktor yang mempengaruhi manajemen pelaksanaan di MTs. Hadil Ishlah, adapun metode penelitian yang digunakan ialah metode kualitatif dengan pendekatan studi kasus, dan teknik pengumpulan data yaitu dengan wawancara, observasi dan dokumentasi, hasil penelitian menjelaskan bahwa manajemen pelaksanaan mata pelajaran bahasa Arab di MTs. Hadil Ishlah meliputi tiga hal yaitu: 1) kepemimpinan, untuk tercapainya tujuan organisasi sekolah kepala sekolah sebagai manajer di sekolah selalu memberikan bimbingan, arahan, dan pengawasan, begitu juga dengan gaya kepemimpinan guru yang demokratis. 2) motivasi, selain kepala sekolah guru di sekolah juga selalu memberikan motivasi terhadap peserta didik baik itu berupa pujian, gaji, hadiah dll. 3) komunikasi, adapun komunikasi yang digunakan disekolah sangatlah baik sehingga terjalinnya kerjasama yang baik antara anggota organisasi sekolah